PENGARUH ORIENTASI PASAR DAN INOVASI PRODUK TERHADAP KEUNGGULAN BERSAING PADA USAHA RUMAH KREATIF PT. SEMEN BATURAJA - Rr Dimas Veronica Priharti; Tati Herlina; Nurul Hakiki (KOLEGIAL, 2021)
This study discusses the influence of market orientation and product innovation on competitive advantage in the creative home business of PT. Semen Baturaja. The data collection technique used in this study is through questionnaires. The number of samples in this study are 69 people. The analytical method used is a quantitative method using multiple linear regression analysis tools. Based on the results of the analysis that has been done, it can be concluded that both partially and simultaneously Market Orientation and Product Innovation have an influence on Competitive Advantage in the creative home business of PT. Semen Baturaja. The coefficient of determination (R Square) is 0.792. It means that the contribution of the influence of the Market Orientation and Product Innovation variables on Competitive Advantage is 79.2%, while the remaining 20.8% is influenced by other variables, such as price or value, pleasing consumers, notable product attributes, and unique service privileges (Saiman, 2014: 124)